Dynamics of Ketamine-induced Loss and Return of Consciousness across Primate Neocortex. (April 2020) - Ballesteros, Jesus J.; Huang, Pamela; Patel, Shaun R.; Eskandar, Emad N.; Ishizawa, Yumiko
Abstract : Background: Ketamine is a noncompetitive N -methyl-D-aspartate antagonist and is known for unique electrophysiologic profiles in electroencephalography. However, the mechanisms of ketamine-induced unconsciousness are not clearly understood. The authors have investigated neuronal dynamics of ketamine-induced loss and return of consciousness and how multisensory processing is modified in the primate neocortex. Methods: The authors performed intracortical recordings of local field potentials and single unit activity during ketamine-induced altered states of consciousness in a somatosensory and ventral premotor network. The animals were trained to perform a button holding task to indicate alertness. Air puff to face or sound was randomly delivered in each trial regardless of their behavioral response. Ketamine was infused for 60 min. Results: Ketamine-induced loss of consciousness was identified during a gradual evolution of the high beta-gamma oscillations. The slow oscillations appeared to develop at a later stage of ketamine anesthesia. Return of consciousness and return of preanesthetic performance level (performance return) were observed during a gradual drift of the gamma oscillations toward the beta frequency. Ketamine-induced loss of consciousness, return of consciousness, and performance return are all identified during a gradual change of the dynamics, distinctive from the abrupt neural changes at propofol-induced loss of consciousness and return of consciousness. Multisensory responses indicate that puff evoked potentials and single-unit firing responses to puff were both preserved during ketamine anesthesia, but sound responses were selectively diminished. Units with suppressed responses and those with bimodal responses appeared to be inhibited under ketamine and delayed in recovery. Conclusions: Ketamine generates unique intracortical dynamics during its altered states of consciousness, suggesting fundamentally different neuronal processes from propofol. The gradually shifting dynamics suggest a continuously conscious or dreaming state while unresponsive under ketamine until its deeper stage with the slow-delta oscillations. Somatosensory processing is preserved during ketamine anesthesia, but multisensory processing appears to be diminished under ketamine and through recovery. Abstract : In a study of nonhuman primates and continuous ketamine administration, the authors demonstrate a unique and gradual evolution of high-frequency and low-frequency neural activity, which distinguish the effects of ketamine from the dynamics of propofol-induced unconsciousness.